Establishment of exclusion responding in children with autism spectrum disorder. (18th September 2018) - Sivaraman, Maithri; Bhabu, Priyanka
Abstract : This study aimed to teach auditory–visual relations using exclusion training and test the emergence of exclusion responding in novel relations and naming by exclusion in four participants diagnosed with autism spectrum disorder. The treatment package consisted of multiple exposures to exclusion trials, prompting, and reinforcement. Four types of matching‐to‐sample trials (baseline, control, exclusion, and probe trials) and naming trials were used during the study. The auditory–visual matching to sample responses and naming responses of the new stimuli was tested. Three out of four participants demonstrated positive learning outcomes with the auditory–visual relations that were taught. One out of four participants demonstrated naming by exclusion. Posttest results show that exclusion responses generalized to stimuli used beyond training for the three successful participants. The results indicate that the treatment package can likely be an important teaching technology to establish exclusion responding.